Empowering local wisdom for enhancing students' social skills in the global era - Dewi Satria Ahmar; Muhammad Fath Azzajjad (Journal of Education, Social & Communication Studies, 2025)
In the era of globalization, preserving local cultural identity poses a significant challenge, especially within the educational context. This study aims to explore how integrating local knowledge into the classroom can enhance the social skills of secondary school students in Palu City, particularly in fostering empathy, cooperation, and conflict resolution. The research employed a quantitative methodology involving a survey of 152 students from various educational institutions, including public and private high schools, vocational schools, Islamic schools, and Islamic boarding schools. Data were collected through questionnaires distributed both offline and online. The instrument comprised five variables focusing on the application of local wisdom and the development of students’ social skills. The analysis revealed that students perceive a positive correlation between the use of local knowledge and the improvement of their social competencies. Approximately 70% to 80% of respondents agreed that incorporating values such as mutual respect, cooperation, and adat-based leadership into learning had positively impacted their behaviour and interactions. The findings highlighted significant improvements in students’ empathy, collaborative abilities, and conflict resolution skills when local cultural principles were embedded in educational content. In conclusion, the study demonstrates that empowering local wisdom within the classroom environment not only contributes to the preservation of cultural identity but also plays a critical role in nurturing essential social skills among students. By embracing local knowledge, educators can better equip students to navigate the challenges of a globalized world while remaining rooted in their cultural heritage. This approach serves as a strategic educational response to globalization, promoting both cultural sustainability and student development.